A red-NIR fluorescent dye detecting nuclear DNA G-quadruplexes: in vitro analysis and cell imaging. Issue 14 (2nd February 2017) - Doria, F.; Nadai, M.; Zuffo, M.; Perrone, R.; Freccero, M.; Richter, S. N.
Abstract : Light-up of nuclear G-quadruplex DNA in cells by an aggregating and red/NIR emitting dye. Abstract : Aggregation, red-NIR emission and light-up upon nucleic acid G-quadruplex binding have been investigated for a prototype core-extended naphthalene diimide, which is capable of fast cellular entry and nucleolar localization. Both high-level colocalization with an anti-G-quadruplex antibody and nucleolin displacement reveal that the compound targets and thus makes visible nuclear DNA G-quadruplexes.